Tooth whitening: technique and aesthetics - Literature review (Research, Society and Development, 2022)
Introduction: Currently, it is known that the main way to whiten teeth is through the use of whitening materials, such as hydrogen peroxide and carbamide peroxide. Objective: To understand the current scenario of tooth whitening. Methodology: In order to carry out this article, a qualitative literature review method was chosen. Results: Teeth whitening is one of the most known and used techniques in the dental office, knowledge of the technique is extremely important, as well as its side effects and indications Results and discussions: The aesthetic condition is recommended by today's society, a factor that brings consequences such as: decreased self-esteem and socialization, especially in younger individuals. Conclusion: Teeth whitening is one of the most sought after procedures in dental clinics around the world. The main factor involved in this search is the aesthetics of the smile, which is demanded by society with increasingly whiter and aligned teeth.